Thermo-hydraulic rating of a shell and tube heat exchanger for acetone cooling using bell-delaware method (Nexo Revista Científica, 2023)
Shell and tube heat exchangers are becoming the most popular devices for the transfer of heat in industrial process applications. In the present work, the thermo-hydraulic rating of a shell and tube heat exchanger proposed to cool an acetone stream was carried out using the Bell-Delaware methodology. An overall heat transfer coefficient value of 426.70 W/m2.K, a calculated heat transfer area of 121.46 m2, and a percent excess area of 20.83% were obtained. Both the pressure drop of acetone and water had values of 1,622.36 Pa and 3,020.46 Pa, respectively. The proposed shell and tube heat exchanger can be used satisfactorily for the required application, since the percent excess area does not exceed the 25%, and the pressure drops of both fluid streams are below the limit values established by the process.